Rehabilitation Of Narcotic Abuse Victims: (Integrated Assessments from National Narcotics Board of Indonesian Republic) - Susiyanto, Randy Pradityo, Rosyidin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Objective: Rehabilitation is a way to save victims of addiction to drug abuse. Therefore, it is well-defined as an effort to restore victims or narcotics addiction for having normal life; physically , mentally and healthy as well, as a result they are able to adjust and improve their skills, knowledge, intelligence, socialization within society or their own families, all above upon is known as resocialization. Method: The research used Socio Legal method, as a legal research method, this is a forum for providing other sciences of law, the field of legal science is always insufficient. Result: This expected can discuss comprehensively the integrated assessment pattern the context of rehabilitating victims of narcotics abuse held by Indonesian National Narcotics Agency, as well as analyzing constraints and problems related to the implementation of legal regulations or policies related to rehabilitation for victims of narcotics abuse. Moreover, hopefully, this research can find appropriate and targeted recommendations for victims and policies as well. Conclusion: Integrated Assessment Team process will be carried out for clients, this process is a recommendation for clients for conduction rehabilitation or not complete. Application process to operate the main clinic of the National Narcotics Agency can be realized as soon as possible, so it has its own place for inpatient